PHARMACOLOGICAL SUPPORT ORGANIZATION OF ТВ PATIENTS IN SMOLENSK REGION - N. A. Pavluchenkova; A. V. Krikova; E. A. Sakharitova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
The article reflects the features of pharmacological support of tuberculosis patients in Smolensk oblast. The participants of the process are described: the subjects of management, funding, pharmacological support. The differences between funding systems of 2008 and 2012 were characterized.